2011
DOI: 10.1093/cercor/bhq296
|View full text |Cite
|
Sign up to set email alerts
|

Underconnected, but How? A Survey of Functional Connectivity MRI Studies in Autism Spectrum Disorders

Abstract: Growing consensus suggests that autism spectrum disorders (ASD) are associated with atypical brain networks, thus shifting the focus to the study of connectivity. Many functional connectivity studies have reported underconnectivity in ASD, but results in others have been divergent. We conducted a survey of 32 functional connectivity magnetic resonance imaging studies of ASD for numerous methodological variables to distinguish studies supporting general underconnectivity (GU) from those not consistent with this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
340
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 388 publications
(373 citation statements)
references
References 80 publications
19
340
1
Order By: Relevance
“…Similar to the rodent studies, there is increasing evidence from both imaging and neurophysiologic studies pointing to altered brain connectivity as a key feature of the pathophysiology of ASD (Casanova and Trippe 2009;Dinstein et al 2011;Kana et al 2011;Muller et al 2011). Additionally, there is some evidence that the changes in neuronal organization in ASD are differentially expressed with age, marked by early life brain overgrowth including increased neuron number, followed by decreases in both structural volumes and neuron number as the brain ages.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 82%
“…Similar to the rodent studies, there is increasing evidence from both imaging and neurophysiologic studies pointing to altered brain connectivity as a key feature of the pathophysiology of ASD (Casanova and Trippe 2009;Dinstein et al 2011;Kana et al 2011;Muller et al 2011). Additionally, there is some evidence that the changes in neuronal organization in ASD are differentially expressed with age, marked by early life brain overgrowth including increased neuron number, followed by decreases in both structural volumes and neuron number as the brain ages.…”
Section: Aberrant Connectivity In Autismmentioning
confidence: 82%
“…While defining subtypes of ASD based on FC may help to resolve some discrepancies in the literature regarding the nature of FC in ASD, it has been proposed that differences in analysis approaches between studies are the most likely causes of inconsistent results between studies of FC in ASD (Hull et al, 2016). For instance, Muller et al (2011) found that studies supporting the "general underconnectivity" hypothesis of ASD were more likely to not use lowpass filtering and to utilize ROIs as opposed to whole-brain analyses. It has also been reported that removal of the global signal alters group differences in FC observed between participants with ASD and TD participants (Gotts et al, 2013).…”
Section: Limitationsmentioning
confidence: 99%
“…Rs-FCs of DMN are significantly affected by the head motion of participants during fMRI scanning; that is, long-distance correlations are decreased by participant motion, whereas many short-distance correlations are increased [43][44][45][46][47]. To investigate the effect of head motion and motion artifacts in rs-FCs, the root mean square (RMS) of six movement parameters obtained in the realignment process (x-, y-, z translations and x-, y-, z rotations), mean frame-to-frame RMS motion [43] and frame-wise displacement (FD) [45] were calculated for each participant.…”
Section: Head Movement Parametersmentioning
confidence: 99%